A study of the Iranian species of Choeras Mason (Hymenoptera: Braconidae: Microgastrinae), with the description of a new species - Moghaddam, Mostafa Ghafouri; Rakhshani, Ehsan; van Achterberg, Cornelis; Mokhtari, Azizollah (Zootaxa, 2018)
Sampling surveys were conducted in various regions of SE to West of Iran to collect the Microgastrinae specimens during 2013–2016. Reliable diagnostic morphological characters were used for comparing and identification of variable specimens. Four species of Choeras Mason, 1981 (Braconidae: Microgastrinae) from Iran are revised; three are illustrated, of which one is described as new species from SE and W Iran: C. taftanensis Ghafouri Moghaddam & van Achterberg sp. n. Occurrence of C. dorsalis in Egypt, Jordan and Malta, C. tedellae in Bulgaria and C. tiro in Israel and Spain are also first recorded.